Nghiên cứu sự gắn kết CO trên DNA bằng phương pháp hồi phục động lực phân tử bán lượng tử - Vận, Đặng Ứng (Vietnam Journal of Chemistry, 2014)
A semi-quantum molecular dynamics relaxation method has been introduced and applied to study on the adsorption of CO on DNA. Using this method the quantum energy changes and the fluctuation of intramolecular atom distances of the adsorption process have been investigated successfully in the region lying between physical and chemical adsorption which could not be studied successfully by cluster approximation on GAUSSIAN or GAMESS software.